HISTORICAL PROGRESS OF DICTIONARY STUDIES (World Bulletin of Education and Learning, 2026)
This article discusses the significance of working with dictionaries in language learning and its evolution. It also pro
Keywords: Dictionary, lexicography, working with dictionaries, evolution, theoretical foundations of the language system.